STRATEGI KOMUNIKASI KOMISI INDEPENDEN PEMILIHAN KABUPATEN ACEH TENGAH DALAM MENINGKATKAN PARTISIPASI MASYARAKAT PADA PELAKSANAAN PILKADA SERENTAK - MUSTAQIM, MUSTAQIM; Budi, Hasiun; AB, Subhan (Universitas Gajah Putih, 2022)
KPU is a general election organizing agency, it takes hard work and creative efforts in inviting the public to be able to play an active role in the ELECTION, especially the ELECTION. To reveal the problem thoroughly and in depth, the low participation of the community in carrying out elections. Some of them are: laziness, not changing fate, influence of other parties, ethnic issues, saturation of the community towards elections, low trust or disappointment (against election organizers, election participants namely legislative candidates, regional leader candidates and political parties), lack of impetus towards community, public awareness is low. The method used in this research is descriptive qualitative which is useful for providing facts and data regarding the strategy of the Independent Election Commission of Central Aceh Regency in an effort to increase voter participation, then the data is analyzed using John Middleton's communication strategy model. the results of this study found that analysis and audience segmentation must also be carried out by determining who the target audience for the program is running. This analysis is very important because the form of planning will depend on the type of public being faced. Media selection is very important to do by paying attention to each stage of socialization, so conclusions can be drawn about how the Strategy of the Independent Election Commission of Central Aceh Regency in an effort to increase public participation in the Pilkada 1. to strengthen or strengthen the agency or institution 2. face to face socialization. face) and through the media 3. Beginner Voter Education.